2010
DOI: 10.1002/micr.20728
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged ischemia increases severity of rejection in skin flap allotransplantation in rats

Abstract: To investigate the relationship between ischemic time and rejection against allotransplants, vascularized cutaneous flaps from the groin of Brown Norway rats were transplanted to Lewis rats. The ischemic time was set at 1 hour and 6 hours for comparison. Cycrosporine A was used as the immunosuppressant. The results showed more severe rejection in the 6 hours ischemic time group in vivo, and in vitro examination using mixed lymphocyte reaction assay also demonstrated a greater antidonor response in 6 hours-isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Some researchers found that MHC class II moleculars in grafts were up-regulated in grafts [6,7,11]. This observed MHC class II hyperexpression, triggered by the release of IFN-g and other mediators [21], led to the hypothesis that ischemia could increase the immunogenicity of an organ graft.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Some researchers found that MHC class II moleculars in grafts were up-regulated in grafts [6,7,11]. This observed MHC class II hyperexpression, triggered by the release of IFN-g and other mediators [21], led to the hypothesis that ischemia could increase the immunogenicity of an organ graft.…”
Section: Discussionmentioning
confidence: 94%
“…In a model using rat groin flaps, it was reported that severe immune responses were induced when ischemic time at normal temperature was prolonged to 3 or 6 h [10,11]. In view of the fact that grafts harvested from cardiac death donors are always preserved at 4 C before transplantation, it is necessary to have an understanding of the relationship between cold ischemic time and acute rejection.…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence that IRI, an unavoidable complication in the process of Tx, can strongly impact graft quality 15 , augment graft allogenicity 8 , and strengthen the subsequent adaptive immune reaction 68 . In this study, we first demonstrated that complement plays an important role in IRI to VC allografts.…”
Section: Discussionmentioning
confidence: 99%
“…However, our knowledge on the influence of IRI in graft rejection has been gained in studies on solid organ Tx, and it has been proposed that composite tissue allografts are more susceptible to IRI than solid organs because of the heterogenous tissue types that all exhibit different immunogenicity 5 . Little is known about how IRI modulates longer-term outcomes after VCA, but increased ischemia times are associated with more frequent and more severe acute rejections with increased anti-donor lymphocyte proliferation following VCA 68 . Although acute rejection episodes can usually be successfully controlled, the number and severity of these episodes are associated with chronic rejection.…”
Section: Introductionmentioning
confidence: 99%
“…Pertinent issues such as excessive blood transfusion(s), prolonged peripheral limb ischemia (ie, tourniquets), relative hypotension, and extreme operative times (24 -36 hours duration), remain unanswered correlates to graft rejection and require further study. [5][6][7] Although the technical details and methods of execution remain unchanged for each alloflap, when combined into one large operation, the necessary extent, expertise, and synergy of the concomitant surgical team is dramatically increased. 8 In this respect, the total amount of operative time and necessary anesthesia will be amplified.…”
Section: Surgical and Medical Problemsmentioning
confidence: 98%